PENGARUH KINERJA KEUANGAN DAN KEBIJAKAN DIVIDEN TERHADAP REAKSI PASAR - Pratama, Lily Nanda; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to examine the influence of financial performance and dividend policy which consists ofcurrent ratio, debt to equity ratio, return on assets, total assets turn over and dividend payout ratio to themarket reaction. The sample in this research consists of 35 types of observations from food and beveragescompanies which are listed in Indonesia Stock Exchange in 2011-2015 periods. The sample collection techniquehas been done by using purposive sampling. The method analysis has been done by using the regression analysistechniques. The results of this research indicate that partial total assets turn over give positive influence to themarket reaction. It is shown by the results of the t test with its significance is 2.416 0.023 < 0.05. Debt to equityratio and dividend payout ratio give negative influence the market reaction. This is indicated by the result of thet test of debt to equity ratio is -3.127 with its significance of 0.004 < 0.05 whereas the dividend payout ratiogains -3.629 with its significance value is 0.001 < 0.05. While, current ratio and return on assets does not giveany infuence to the market reaction. This is shown by the current ratio and the result of the t test results is0.056 with its significance of 0.956 whereas the return on assets gain value -0.128 with its significance of 0.899.Keywords: financial performance, dividend policy, stock return, stock price.